Utilization of Metal-Layered Plastic Packaging Waste and Eggshell Powder as Partial Substitution Materials in Paving Blocks - Raisha Tassa; Nursyamsi Nursyamsi; Johannes Tarigan (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the utilization of metal-coated plastic packaging waste (WMP) and eggshell powder (ESP) as partial substitution materials in the manufacture of environmentally friendly paving blocks. The method used is an experimental approach in the laboratory with variations of WMP of 5%, 10%, and 15% as aggregate substitutes, and ESP of 5% as cement substitutes. The test specimens were molded using a hydraulic press machine and tested based on SNI 03-0691-1996 standards for compressive strength, water absorption, resistance to sodium sulfate solution, and impact tests. The results showed that the combination of WMP and ESP was able to improve the mechanical performance of paving blocks, especially in the variations of WMP 10% and ESP 5% which produced optimal compressive strength and low water absorption. This study contributes to the development of sustainable construction materials and supports the sustainable development goals (SDGs).